2001
DOI: 10.1063/1.1384860
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen induced positive charge generation in gate oxides

Abstract: Articles you may be interested inHybrid titanium-aluminum oxide layer as alternative high-k gate dielectric for the next generation of complementary metal-oxide-semiconductor devices Appl. Phys. Lett. 86, 042904 (2005); 10.1063/1.1856137 Evaluation of nickel and molybdenum silicides for dual gate complementary metal-oxide semiconductor application Appl. Phys. Lett. 86, 022105 (2005); 10.1063/1.1849850Secondary ion mass spectrometry characterization of source/drain junctions for strained silicon channel metal-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 37 publications
1
18
0
Order By: Relevance
“…However, hole trapping phenomenon alone cannot explain the positive charge trapping characteristics in the bulk of ultrathin SiO 2 . Rather, positive charge trapping in the bulk of ultrathin oxide can be best explained by the cumulative effects of hole trapping in as-fabricated traps possibly originated from bridging oxygen vacancies [1] and captured proton-induced overcoordinated oxygen centers [Si 2 @OH] + [6,9]. These proton-induced defects are most probably generated at the Si/SiO 2 interface, where they are ''stabilized'' by the strain that resides at the interface.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, hole trapping phenomenon alone cannot explain the positive charge trapping characteristics in the bulk of ultrathin SiO 2 . Rather, positive charge trapping in the bulk of ultrathin oxide can be best explained by the cumulative effects of hole trapping in as-fabricated traps possibly originated from bridging oxygen vacancies [1] and captured proton-induced overcoordinated oxygen centers [Si 2 @OH] + [6,9]. These proton-induced defects are most probably generated at the Si/SiO 2 interface, where they are ''stabilized'' by the strain that resides at the interface.…”
Section: Discussionmentioning
confidence: 97%
“…However, little work [6][7][8] has been done in understanding electrical stressinduced degradation of ultrathin SiO 2 in direct tunneling (DT) regime. Furthermore, the origin of positive oxide charge remains a controversy between proton-induced defect generation [1,6,9] and hole trapping [2,4] in as-fabricated traps. In the present work, it is found that electron trapping in SiO 2 film of thickness as low as 2.4 nm is suppressed during CVS with negative gate bias, a behavior contrary to thicker oxides as reported by DiMaria et al [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…For some SiO 2 , it has been reported that forming gas anneal at 450 o C or above can also induce positive charging (28)(29)(30). One way for enhancing the positive charging is to expose SiO 2 to a temperature of 1100 o C or higher (30).…”
Section: Process-induced Positive Chargingmentioning
confidence: 97%
“…Hydrogen enhances positive charging(30). For some Hf-stacks, the FG anneal has little effect on both poly-(a) and TaNgated (b) nMOSFETs.…”
mentioning
confidence: 98%
See 1 more Smart Citation